Comparison of Anti-Glycation Capacity of Two New Purple-Colored- Leaf Tea Cultivars with an Ordinary Green-Colored-Leaf Tea Cultivar in Taiwan - Su-Chen Ho; Min-Sheng Su; Chih-Cheng Lin; Chui-Feng Chiu (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2017)
The special tea varieties with purple- or red-colored leaves have been successfully bred in Taiwan and their health benefits are needed to be evaluated. The aim of this study was to evaluate the phytochemical content, the antioxidant properties, and the anti-glycation capacities of two new purple-colored-leaf tea cultivars (TTES No.113 & 117) and one of the most cultivated teas in Taiwan (TTES No.18). Green tea made from the two purple-colored-leaf tea cultivars, especially the TTES No.117 had significantly higher phenolic, flavonoid, anthocyanin, and catechin content than the TTES No.18. The purple-colored-leaf tea also had higher antioxidant activities including ferric reducing antioxidant power (FRAP) and oxygen radical absorbance capacity (ORAC). The formation of fluorescent advanced glycation end products (AGEs) and non-fluorescent AGEs (Nɛ-carboxymethyllysine; CML) in a glucose/ BSA system were significantly inhibited by teas. The inhibitory capacities of teas on fluorescent AGEs and CML were correlated with phenolics or flavonoids, rather than catechins or anthocyanins. These results implied that the potent antiglycation capacity of purple-colored-leaf tea was primarily attributed to the total phenolics. These findings highlight that the potential use of purple-colored-leaf tea bred in Taiwan as a functional beverage for preventing diabetic complications.